OBTAINING, FORMULATING, AND TABULATING THE ANTHROPOMETRIC DATA OF PARTICIPANTS AND THE RESPECTIVE RESULTS OF CPR MANEUVERS - Thiago, Isabela Marques; Filho, Ilamar José Fernandes; Fontoura, Humberto de Souza (CIPEEX, 2025)
The widespread training of the population in cardiopulmonary resuscitation (CPR) techniques is of fundamental importance to reduce deaths from cardiac arrest. However, the proper dissemination of high-quality CPR is still underperformed in Brazil. This study aims to compare the quality of CPR maneuvers across different periods of the medical course through the development of a data collection and analysis instrument. The study population consisted of 116 students from three different periods at UniEVANGÉLICA. This was a cross-sectional analytical study. Participants provided their anthropometric data, received instructions on proper CPR technique from the researchers, and then performed the maneuver on a CPR manikin equipped with a sensor for evaluation. The results showed that performance was below average across all periods studied, though the eighth period students performed CPR the best. Participant weight and gender had a significant influence, with heavier and male participants performing higher-quality CPR. It was concluded that improvements are necessary in CPR teaching during medical training, emphasizing especially the correct depth of compressions.